2022
DOI: 10.3389/fonc.2022.1065303
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction after resection of C2 vertebral tumors: A comparative study of 3D-printed vertebral body versus titanium mesh

Abstract: BackgroundSurgical resection of C2 vertebral tumors is challenging owing to the complex anatomy of C2 vertebrae and the challenges to surgical exposure. Various surgical approaches are available, but some are associated with excessively high risks of complications. An additional challenge is reconstruction of the upper cervical spine following surgery. In the last decade, additive-manufacturing personalized artificial vertebral bodies (AVBs) have been introduced for the repair of large, irregular bony defects;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…No sources of heterogeneity were identified after the sensitivity and meta-regression analyses ( Tables 2 , 3 ). Therefore, a qualitative descriptive analysis was performed, and the results showed that five studies ( 12 , 13 , 16 – 18 ) reported significantly less intraoperative blood loss in the 3D-printed AVB group than in the conventional TMC group, whereas the remaining three studies ( 14 , 15 , 19 ) reported no significant difference between the two groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…No sources of heterogeneity were identified after the sensitivity and meta-regression analyses ( Tables 2 , 3 ). Therefore, a qualitative descriptive analysis was performed, and the results showed that five studies ( 12 , 13 , 16 – 18 ) reported significantly less intraoperative blood loss in the 3D-printed AVB group than in the conventional TMC group, whereas the remaining three studies ( 14 , 15 , 19 ) reported no significant difference between the two groups.…”
Section: Resultsmentioning
confidence: 99%
“…Early complications mainly included cerebrospinal fluid leakage, pleural effusion or lung infection due to pleural rupture, poor healing of infected wounds, and neurological complications. The occurrence of early complications between 3D-printed AVB (n = 150) and conventional TMC (n = 167) groups was compared in seven studies (12,13,(15)(16)(17)(18)(19). The OR in early complications between two groups was 0.52, significantly inclined toward the conventional TMC group (95% CI: 0.29 to 0.90, P = 0.02; I² = 40%, fixed-effects model; Figure 8).…”
Section: Early Complicationsmentioning
confidence: 99%
“…In our preliminary report of the rst 3D printed C2 vertebral body replacement in 2016, we described this new implant design, which was suitable for the patient's anatomical structure to increase the contact area between adjacent vertebrae, with the additional feature of zero-pro le xation, and improved conduciveness to bone-ingrowth due to their trabecular pores [13]. In 2022, Hu et al of our center conducted a comparative study of conventional titanium mesh and 3D printed AVB for reconstruction after resection of C2 tumor, which showed that personalized AVB can provide reliable reconstruction [21]. Laratta et al proposed that the advantage of 3D printed AVB for postoperative fusion is its dense reticular structure, which can increase the interaction with surrounding bone and promote bone growth inward without bone grafting [22].…”
Section: Discussionmentioning
confidence: 99%
“…In 2014, Ji et al proposed a tailored titanium clivus plate to reconstruct the craniovertebral junction in combination with posterior fixation in order to augment upper cervical stabilization [ 37 ]. In 2022, Hu et al proved that 3D printed vertebral bodies provided reliable reconstruction support comparable with titanium mesh after en bloc resection of C2 tumors [ 32 ]. Indeed, 3D technology has facilitated the process of tailoring such implants to a given patient and has also been reported to be helpful for surgical planning and teaching [ 8 , 51 ].…”
Section: Novelties For Safer Cvj Surgerymentioning
confidence: 99%